Effects of Genipin Concentration on Cross-Linked Chitosan Scaffolds for Bone Tissue Engineering: Structural Characterization and Evidence of Biocompatibility Features - Simona Dimida; Amilcare Barca; Nadia Cancelli; Vincenzo De Benedictis; Maria Grazia Raucci; Christian Demitri (International Journal of Polymer Science)
Genipin (GN) is a natural molecule extracted from the fruit of Gardenia jasminoides Ellis according to modern microbiological processes. Genipin is considered as a favorable cross-linking agent due to its low cytotoxicity compared to widely used cross-linkers; it cross-links compounds with primary amine groups such as proteins, collagen, and chitosan. Chitosan is a biocompatible polymer that is currently studied in bone tissue engineering for its capacity to promote growth and mineral-rich matrix deposition by osteoblasts in culture. In this work, two genipin cross-linked chitosan scaffolds for bone repair and regeneration were prepared with different GN concentrations, and their chemical, physical, and biological properties were explored. Scanning electron microscopy and mechanical tests revealed that nonremarkable changes in morphology, porosity, and mechanical strength of scaffolds are induced by increasing the cross-linking degree. Also, the degradation rate was shown to decrease while increasing the cross-linking degree, with the high cross-linking density of the scaffold disabling the hydrolysis activity. Finally, basic biocompatibility was investigated in vitro, by evaluating proliferation of two human-derived cell lines, namely, the MG63 (human immortalized osteosarcoma) and the hMSCs (human mesenchymal stem cells), as suitable cell models for bone tissue engineering applications of biomaterials.